Information heterogeneity and intended college enrollment - Zachary Bleemer; Basit Zafar (Federal Reserve Bank of New York, 2014)
Despite a robust college premium, college attendance rates in the United States have remained stagnant and exhibit a substantial socioeconomic gradient. We focus on information gaps - specifically, incomplete information about college benefits and costs - as a potential explanation for these patterns. In a nationally representative survey of U.S. household heads, we show that perceptions of college costs and benefits are severely and systematically biased: 74 percent of our respondents underestimate the true benefits of college (average earnings of a college graduate relative to a non-college worker in the population), while 77 percent report public college costs that exceed actual sticker costs. There is substantial heterogeneity in beliefs, with larger biases for the more disadvantaged groups, lower-income and non-college households. We show that these biases are problematic since they (indirectly) impact the respondents' reported intended likelihood of their (pre-college-age) child attending college. We simulate an "information intervention", and find that were individuals to be provided with the correct population distribution of college costs and returns, the intended child's college attendance would increase significantly, by about 0.2 of the standard deviation in the baseline intended likelihood. Importantly, as a result of the simulated intervention, gaps in college attendance by household income or parents' education persist but decline by 30 to 50 percent.
Keywords: D81; D83; D84; I21; I24; I28; 330; college enrollment; college returns and costs; information; subjective expectations